States in generalized probabilistic models: An approach based in algebraic geometry - Massri, Cesar Dario (2019)
We present a characterization of states in generalized probabilistic models by appealing to a non-commutative version of geometric probability theory based on algebraic geometry techniques. Our theoretical framework allows for incorporation of invariant states in a natural way.